Um estudo descritivo sobre as manifestações da ambiguidade lexical em Libras - Martins, Tânia Aparecida (2013)
This essay has the aim to fulfill a descriptive study regarding the lexical ambiguity of the Brazilian Sign Language Libras through the investigation of the specialty literature, culminating with the construction of a data with ambiguous lexical items containing, respectively in two dictionaries considered bilingual: The dictionary of the Brazilian Sign Language/Libras version 2.0, 2008 (digital) and the The New Deit-Libras Trilingual Illustrated Encyclopedic Dictionary (2012). To the general studies about this subject, it was regarded the basis of the structuralist semantics founded in researches of investigators, some of them were: Ullmann (1964), Saussure (1987), Câmara Jr (1970) and Silva (2006). Based also in Emmorey (2002), Johnston & Schembri (2007), Ferreira Brito (1995) and Quadros & Karnopp (2004), the criteria that would found the setting of data was established so that the records and analysis were made. This study was conducted by a collection of questions that include our concern to know how the lexical ambiguity that is shown in Libras; how the users of this language deal with this kind of situation, which effects this phenomenon causes in the comprehension of the deaf and yet what competences and abilities the deaf develop or need to develop to clarify mostly the sings that are lexically ambiguous. In the bias of the specialized literature regarding the studies of the meanings and the significations of the words, it´s assumed that the lexical ambiguity is caused when a sign/word has two or more meanings/significations, when comparing the contexts. Through the general distinction between polysemy and homonymy, it was concluded that in Libras, differently from the Portuguese Language, the lexical ambiguity can be shown in three different forms: (i) through the homonymy; (ii) through the polysemy; and through the world knowledge and determining evocative (religious, cultural, social and others). This way, homonymy is considered the situation in which the meanings of the same word don´t show any semantic relation and polysemy when the meanings/significations admitted by a word/sing meet the points of a semantic contact. The representative meaning of FRIDAY and FISH, for instance, although semantically not related, are part of a meaningful group of others signs that the same effect occurs. We call them evocative traces (traces determined by relations either religious or cultural or others), we couldn t classify them as cases of homonymy, neither polysemy. Thus, we created a third kind of ambiguity. When the phenomenon of the lexical ambiguity is analyzed, in general, some authors will say that, in fact, the marks of the available resources of the language (the marks, such as, the references of the enunciatively space, the alteration of the movement of the hands or the other expressions), they would be enough to differ them. Anyway, many cases and analyzed this study, it could be observed that, even being useful, they are not able to solve or clarify all the ambiguous items